2016
DOI: 10.1177/247553031600100207
|View full text |Cite
|
Sign up to set email alerts
|

Physician Satisfaction with Current Psoriasis Treatment: A Real-World Study in the USA

Abstract: Background: Dermatologists may provide a unique perspective on psoriasis management by offering an evaluation of satisfaction with disease control. Objectives: To examine physician satisfaction with psoriasis control. Methods: Data were extracted from the Adelphi 2011/2013 Psoriasis Disease Specific Programmes, two real-world U.S. surveys of dermatologists. For individual patients, physicians reported treatment history, disease severity, symptom severity for itching, pain and scaling, and their satisfaction le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Patients' interpersonal relationships, social activities, sexual life and self-esteem are commonly adversely affected by chronic dermatological diseases [14]. In addition, patients may be dissatisfied with treatments and healthcare in general.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' interpersonal relationships, social activities, sexual life and self-esteem are commonly adversely affected by chronic dermatological diseases [14]. In addition, patients may be dissatisfied with treatments and healthcare in general.…”
Section: Introductionmentioning
confidence: 99%
“…Some treatment guidelines now consider patient‐reported measures, such as the Dermatology Life Quality Index (DLQI), in addition to physician‐reported measures, when defining treatment goals and success or failure of a given regimen . This is important because many psoriasis patients report treatment dissatisfaction, which can contribute to depression, anxiety, avoidance of medical care and poor adherence to prescribed treatments. To maximize patient satisfaction and adherence as well as to treat the signs and symptoms of psoriasis, a treatment should act rapidly to clear the skin, improve pruritus and pain and positively impact HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a wide range of therapeutic options currently available for psoriasis, recent studies indicate low levels of patient satisfaction with many of these treatments. 1-5 Understanding patients’ concerns and the drivers behind their dissatisfaction is crucial as this may allow clinicians to modify therapeutic approaches to improve care from the patient’s perspective. As satisfaction with treatment has been associated with improved adherence and persistence, the implications toward achieving optimal outcomes have the potential to be significant.…”
Section: Section V Management Of Psoriasis In the Era Of Il-17–targementioning
confidence: 99%
“…According to a study by Korman et al 4 involving more than 600 patients, an increase in disease severity and psoriasis-related itching, pain, and scaling were identified as important contributors to treatment dissatisfaction in greater than 50% of patients, including almost one-third of the patients treated with biologics. A large, multinational, population-based survey of psoriasis and/or psoriatic arthritis (PsA) patients in North America and Europe (the MAPPP [Multinational Assessment of Psoriasis and Psoriatic Arthritis] survey) 5 revealed that approximately half of the patients who had received biologic therapy discontinued therapy, most often for safety/tolerability reasons and a lack/loss of efficacy.…”
Section: Section V Management Of Psoriasis In the Era Of Il-17–targementioning
confidence: 99%